The effect of various milling processes on sorghum grain when used for finishing fall pigs in drylot - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Six lots were self-fed, free choice, in drylot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. Each ton of mixed protein supplement also contained 27 pounds of Aurofac and ½ pound of zinc oxide. The ration for each lot varied only in the method of processing.
Keywords: Swine; Milling; Sorghum grain; Drylot